2020
DOI: 10.1080/17461391.2020.1845816
|View full text |Cite
|
Sign up to set email alerts
|

Delayed potentiation effects on neuromuscular performance after optimal load and high load resistance priming sessions using velocity loss

Abstract: Aim: (i) to compare the effects of two different low-volume resistance priming sessions, where the external load is modified on neuromuscular performance after 6 h of rest; and (ii) to identify the effects on psychological readiness in participants with resistance training experience. Methods: Eleven participants (Body mass: 77.0 ± 8.9 kg; Body height: 1.76 ± 0.08 m; Half squat repetition maximum: 139.8 ± 22.4 kg) performed the priming session under three experimental conditions in a randomized and cross-over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(66 citation statements)
references
References 58 publications
3
62
1
Order By: Relevance
“…All participants carried out the jumps at the same time of day. The same standardized warm-up was performed before each session which included 5 min of cycling with a rate of perceived exertion (RPE) of 5/10, 3 min of hip, knee and ankle mobility and 10 bodyweight squats [ 18 ]. Participants followed the instructions to jump as high as possible and received the same verbal encouragement during the trials.…”
Section: Methodsmentioning
confidence: 99%
“…All participants carried out the jumps at the same time of day. The same standardized warm-up was performed before each session which included 5 min of cycling with a rate of perceived exertion (RPE) of 5/10, 3 min of hip, knee and ankle mobility and 10 bodyweight squats [ 18 ]. Participants followed the instructions to jump as high as possible and received the same verbal encouragement during the trials.…”
Section: Methodsmentioning
confidence: 99%
“…An a-priori sample size estimation revealed that a minimum of six participants were required for a within-factors repeated measures ANOVA assuming a partial eta-squared (η 2 ) of 0.533 for CMJ [7], with a repeated measures Pearson´s correlation of 0.98 and values of 5% and 1% for type I and type II errors, respectively. However, 14 active young participants (10 males and 4 females), were recruited for this study (Mean±SD: body mass (BM): 73.2±13.4 kg; height: the informed consent and performed a standardized warm-up as previously described [7]. After warming-up, participants performed three CMJs with 30 seconds rest between attempts.…”
Section: Participantsmentioning
confidence: 99%
“…jumping strategy (Table 3). To our knowledge, only a handful of studies have evaluated different vertical jump metrics after velocity-based resistance priming exercises [7,10,26].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations